Becoming Other: Cannibalistic Translation as Liminal Transformation - Young, Jake (TTR, 2023)
Combining the translation theory of Haroldo de Campos and Eduardo Viveiros de Castro’s analysis of Indigenous metaphysics, this essay argues that the metaphorical consumption or cannibalization of texts through translation highlights the role literary influences play in expanding and transforming global literary networks. An understanding of how translated texts consume the source text in the process of their transcreation reveals a rhizomatic exchange and circulation of literature that destabilize at once traditional power structures and conventional translation binaries that give precedence to questions of originality and fidelity. Specifically, attention to rhizomatic literary influences acknowledges the inherent power dynamics and inequalities within postcolonial literature. A cannibalistic view of translation brings into focus these implicit power imbalances while also offering translation as a means to subvert and transform language and cultural hierarchies. Cannibalistic translation recognizes translation as a liminal process of becoming other that transforms not only the source and target texts but also the translator, readers, and literary networks, a process that reverberates through the dialogical relations connecting them all. By drawing on Viveiros de Castro’s works on Indigenous Amazonian ontologies, this article demonstrates ways in which the cannibalistic translation theory of the de Campos brothers can continue to be refined.